MORAL VALUES AND THEIR GOOD IMPACTS IN HACKSAW RIDGE MOVIE BY MEL GIBSON - Ahmad Nurjani; Sulaiman Sulaiman; Dedi Efendi (Universitas Muara Bungo, 2018)
This research analyzes about the moral values and their good impacts in Hacksaw Ridge movie by Mel Gibson. The goals of this research are to explain the moral values and the good impacts of moral values itself from this movie. In this research, the writer uses descriptive qualitative method, because it helps the writer to explain the data in the form of phrase and sentence. The data is analyzed through some ways: identify, classify, analyze, and conclusion. The writer describes and analyses sentences from conversation of characters in Hacksaw Ridge Movie that contain moral values within it. There are two kinds result in this research, they are moral values and their good impacts. Moral values that the writer found from this movie are moral values of being, such as honesty, courage, peace ability, self-discipline, self reliance and potential, and moral values of giving, such as loyalty, respect, love, and unselfishness. The writer also found some good impacts of these moral values. First, moral value can improve someone’s high self confidence. Second, moral value make someone has patience. And third, moral value can create someone’s care. Key words: Good impact, Hacksaw ridge, Moral value.